Efecto in vitro del zumo de vaccinium corymbosum l. sobre escherichia coli - Adrianzen Ramirez, Jilwer Joel (2017)
This study aimed to evaluate the effect of juice Vaccinium corymbosum L. on the in vitro growth of Escherichia coli strain. The strain used was reactivated in Müller Hinton broth and incubated for 18 hours at 37 ° C. Then a roast of the bacteria was taken and adjusted with saline solution turbidity standard Mac Farland No. 0.5 (1.5x108 CFU / mL) for the conduct of the trial proceeded to determine the minimum bactericidal concentration (MBC) and the concentration minimal inhibitory (MIC). The results show an inhibitory effect of juice Vaccinium corymbosum L. on Escherichia coli, have a lower turbidity medium containing Escherichia coli in 50uL 100% v / v for the minimum bactericidal concentration (MBC) was evident that the juice Vaccinium corymbosum L. spreads on the strain of Escherichia coli, at the concentration of 100% v / v, showing a halo of 4 mm in diameter